Dissolved State and Identity in John Maxwell Coetzee’s Life and Times of Michael K within the scope of the Postcolonial Other - İsmail Avcu (Ideas: Journal of English Literary Studies)
Regardless of the situation, human rights are expected to be maintained and safeguarded and it can be inferred from this that such rights are automatically terminated in times of war. Michael K’s futile attempts to obtain travel documents to Cape Town lawfully serve as an example of how much people rely on the efficient operation of all governmental institutions, while his entire life demonstrates the significance of personal freedom and freedom of movement. Michael K keeps quiet, not only because he is alone for most of his life, but also because silence is a subliminal kind of resistance. It makes no difference if Michael K is conscious of his heroic resistance or not; what counts is that he says very little because he has nothing to say. He is reluctant to share his tale. He does not want to be recognised, perceived, or misinterpreted. This paper dwells on issues of dissolution of the individual, silence, other, state, and the position of the traumatised and the otherised in the gruesome and cruel apartheid in South Africa in John Maxwell Coetzee’s Life and Times of Michael K. For the discussion of the novel, the theoretical basis of the concepts such as the other, dissolution of state and silence are formed with reference to prominent postcolonial theorists’ views.